Meta-analysis of the occurrence of hepatocellular carcinoma after the treatment of entecavir and tenofovir for chronic hepatitis B. Issue 6 (10th February 2023) - Tang, Kaiyue; Cheng, Huizhen; Wang, Haiyan; Guo, Yueping
Abstract : Background: Tenofovir and Entecavir are recommended as the first-line medicine of treatment for chronic hepatitis B. The occurrence of hepatocellular carcinoma after the treatment of chronic hepatitis B is a major problem. For the time being it is still unclear whether there remains a difference in risk correlation of hepatocellular carcinoma after the treatment of Tenofovir and Entecavir for chronic hepatitis B. Since previous studies have raised different ideas, this article aims to come to a conclusion targeting such a topic through analyzing the latest data. Methods: We searched some databases, such as PubMed, Web of Science, and Cochrane Library, for related studies on patients with chronic hepatitis B receiving the treatment of Tenofovir and Entecavir and then developing hepatocellular carcinoma. The search time was set to begin from the establishment time of the above-mentioned databases to May 2022. Two researchers were designated to screen the literature independently according to the inclusion and exclusion criteria set in this study; they then evaluated the quality of the literature included and extracted the data. Revman 5.3 software was used for meta-analysis. Results: After screening the literature, a total of 20 pieces of cohort study literature conformed to the inclusion criteria. Among which were 62, 860 cases of patients receiving Entecavir, and 27, 544 cases of patients receiving Tenofovir; there were 3669 cases with the occurrence of hepatocellular carcinoma in the Entecavir group and 1089 cases with the occurrence of hepatocellular carcinoma in Tenofovir group. The result of Meta analysis of these 20 pieces of literature shows that compared with the Tenofovir group, the Entecavir group has a lower occurrence rate of hepatocellular carcinoma, and the difference is statistically significant. The results are expressed as odd ratio (OR) and 95% confident interval (95%CI), (OR = 1.66, 95%CI: 1.35–2.05, P < .05). The result of Meta analysis of 10 studies related to Korea shows that the occurrence rate of hepatocellular carcinoma in the Tenofovir group is lower than that of the Entecavir group, and the difference is statistically significant (OR = 1.59, 95%CI: 1.29–1.95, P < .05). The result of meta-analysis of 5 studies related to China shows that the occurrence rate of hepatocellular carcinoma of Tenofovir group is lower than that of Entecavir group, and the difference is statistically significant (OR = 2.35, 95%CI: 1.15–4.81, P < .05). Conclusion: The occurrence rate of hepatocellular carcinoma after the treatment of tenofovir for chronic hepatitis B is lower than that of the treatment of entecavir.